Summary of the Experience in the Diagnosis and Treatment of Complex Preauricular Fistulas in 78 Children - Xu, Ying; Seng, Dongjie; Jiang, Lan; Wang, Shengcai; Ni, Xin; Zhang, Jie; Han, Fugen (Frontiers in Surgery, 2021)
Objective: This study aimed to investigate the application of mini-incisions in complex preauricular fistula resection in children. Methods: A total of 78 children who were diagnosed with infectious preauricular fistula from January 2017 to December 2019 were included in the study. Their clinical data were analyzed retrospectively, and surgical treatment with mini-incisions based on plastic surgery principles and techniques was provided. Results: All patients achieved healing by first intention. The patients were followed up with for 6–42 months, and no recurrence or local auricular deformation occurred. Conclusion: The application of mini-incisions and plastic surgery techniques in complex preauricular fistula resection in children can achieve a good effect and improve the satisfaction of the children and their parents.